PERANCANGAN KONSEP FIREFIGHTING SYSTEM TIPE PELONTAR DRY CHEMICAL POWDER BALL PADA DRONE PT. CI - Riky Adhiharto; Rahmat Arta, Fauzan (BAROMETER, 2024)
Fire is an emergency condition that does not know the situation or time when it can occur and is difficult to control which can cause material loss and life safety. In a fire there is what is called the Flammable Range, which is the limit between the minimum and maximum concentration of a mixture of fuel vapor and air (oxygen) which can explode or ignite at any time if a heat source is provided. Range, place, time and security factors are the main causes of the difficulty of the fire control process. In order to help and simplify the process of extinguishing fires, a tool was developed that can be used in fighting fires. This tool is expected to be able to throw a ball-shaped type of dry chemical powder fire extinguisher, because it is faster and more effective for extinguishing fires in tall buildings so that the fire does not spread and cause more fatal damage. This tool is called a firefighting system, which utilizes drone or Unmanned Aerial Vehicle (UAV) technology. Drones and firefighting systems are flown to reach high places, avoid obstacles, and can fly long distances with the aim of minimizing risks that threaten safety in controlling fires. This research uses the VDI 2222 (Verein Deutsche Inginieuer 2222) design method, starting with problem identification, selecting alternative concept variations, determining component specifications, construction calculations and detailed design. Alternative Variation Concept 1 was obtained as the selected design concept, with a score of 420 (84%) for the Technical Assessment and a score of 360 (72%) for the Economic Assessment. This fire fighting system has installation dimensions on the drone of 600x600x400 mm, the weight of the tool and 3 balls is 12 kg, the throw distance is 5.05 m, the initial speed is 15,6604 m/s, the target can be at a height of 9,512 m.